Efektivitas Pemanfaatan Dan Penerapan E-Learning Pada Matapelajaran Prakarya Dan Kewirausahaan Terhadap Prestasi Siswa Kelas X Smk Muhammadiyah 1 Sukoharjo Tahun Ajaran 2016-2017 - Wirantika, Dara; , Suranto, S.Pd.,M.Pd (2017)
The purpose of this research is to know the influence in a partial and simultaneous the effectiveness of the use and application of e-learning on entrepreneurship matapelajaran against student achievement class x smk muhammadiyah 1 ukoharjo 2016-2017 academic year. 2 The research is research associative done to look relation between one variables with other variables .The cause and effect .So the pulation of the research is all students x smk muhammadiyah 1 ukoharjo 454 with as many as 200 students as sample .Using probability of sampling to technique simple random sampling .Engineering data collection by using the method survey has tested by test and the validity of normality .Analysis techniques the data used was multiple regression , the t , the f , contributions relatively and contributions effective. Based on the analysis t test , can be seen that the effectiveness of the utilization of variable e-learning (X1) having value t count as much as 2,988 with value t table worth 1,972 ho rejected then and hi accepted because t count > ttable which means there are significant influence between the effectiveness of the utilization of e-learning (X1) against student achievement (Y) on the subjects of entrepreneurship class x smk muhammadiyah 1 sukoharjo 2016-2017 academic year . To the application of elearning variable (X2) having value t count as much as 1,986 with value t table worth 1,972 ho rejected then and hi accepted because tcount > ttable which means there are significant influence between the application of e-learning (X2) against student achievement (Y) on the subjects of entrepreneurship students against achievement class x smk muhammadiyah 1 sukoharjo 2016-2017 academic year Virtue of the f that was done on this research showing that the f count of 15,727 > f table of 3,04 with the probability of 0,000 ( pvalue & it; 0,05 ).This means is the simultaneously between the effectiveness of the use of e-learning (X1) and application of e-learning (X2) against a student achievement x smk muhammadiyah 1 sukoharjo academic year 2016 / 2017. Based on the results of analysis, r2 value of 0,138 means the second set of effectiveness e-learning (X1) and application of e-learning (X2) having influence of 13,8 %.The remaining of 86,2 % described by other variables out this research